The Synthesis, Characterization and Biological Activity of Some Metal Ions Complexes with Schiff’s Bases Derived from Reaction of 3-Hydrazone-1,3- Dihydro-Indole-2-One with 2- Pyridine Carboxaldehyde - sami Muwafaq, safa; Shaalan, Naser (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
Novel complexes were synthesized from Schiff base ligand (L) produced by reacting 3-hydrocyclo-1,3-dihydro-indole-2-one (A) with 2-pyridine carboxaldehyde in an ethanol medium. This study aims to synthesize the metal Schiff base ligands complexes of heterocyclic, which tested their biological activity as antimicrobial drugs. Metal complexes comprising manganese, cobalt, nickel, copper, and zinc with Schiff base have been produced at a molar ratio of 1:1 (M: L). These complexes were identified using M.P, FT-IR, UV-Vis, Mass, 1H-NMR, and C.H.N. Chloride-containing, atomic absorption, molar conductance, and magnetic susceptibility have all been used to identify these compounds. Utilizing mass spectroscopy, the molecular ion peak was found at m/e 251.01, confirming the formula weight for L, which matches the estimated m+ value (250.26). The results show a hexadentate coordination geometry for each complex and the ligand with good yield. This study emphasizes the importance of using a metal complexation method to stabilize ligands and increase their bioactivity. The biological activities of the new compounds were valued against Gram-positive (Escherichia coli) and Gram-negative (Staphylococcus aureus). Hence, their results were good in inhibition.